Study of microbial pattern and antibiotic sensitivity pattern in hospitalised acute exacerbation of COPD patients - R., Raveendra K.; Rejeev, Devapriya; kodur, Nandan (International Journal of Advances in Medicine, 2019)
Background: Most of the acute exacerbations of COPD are preventable and curable. More than 50% of them are infectious in nature and strain of the pathogen causing them is quite variable from place to place and often determines the severity of exacerbation. Antibiotic resistance has created a bigger challenge for the treating physicians to have a better treatment outcome. Our objective was to study the bacterial profile and antibiotic sensitivity pattern in all acute exacerbation of hospitalized COPD patients. Methods: All patients admitted for COPD exacerbation were evaluated for their sputum culture and sensitivity and followed up. Results: Totally 148 patients were included in the study and organisms were isolated 72 patients. Important organisms isolated were Klebsiella (20), Pseudomonas (16), Streptococci (8), Staphylococcus aureus (8), MTB (4) etc. Many MDR strains were noted. Resistance to newer antibiotics were also noted.64 patients out of 148 required a change in antibiotic (40 in culture positive group, 24 in culture negative group) and there were 12 deaths noted in study. Mortality and morbidity were more in culture negative group and in those who had MDR strains. Conclusions: Gradual shift to gram negative bacilli was observed in infective exacerbation of COPD. Multiple resistant strains were noted and often responsible for poor recovery. Early diagnosis and proper antibiotic selection is the key for a good treatment outcome.